Proposed instructional materials on the teaching of multiplication to educable mentally retarded children at the intermediate level - Amolat, Herminia Macaraig 1947-; Sison, Waldetrudes Montojo (Quezon City College of Education, University of the Philippines Diliman, 1977)
This paper proposed instructional meterials on teaching multiplication to educable mentally-retarded children at the intermediate level and to help teachers and school administrators gain a common background on programmed instruction and to adapt its principles effectively in preparing instructional materials. This material, written in Filipino, used the linear type of programming. The body of information was broken down into frames consisting of a series of items, drills, and exercises regarding the material. Six mentally-retarded children at the intermediate level were selected for this experiment. Due to the limitations of the proposed instructional material, more try-outs and revisions were recommended for the material to be expanded to a complete unit on multiplication.
Vita.
Thesis (Master of Arts in Teaching Special Education - Mental Retardation)--University of the Philippines, Diliman
Keywords: Children with mental disabilities -- Education (Elementary) -- Philippines -- Manila; Multiplication -- Study and teaching (Elementary) -- Philippines -- Manila; Teaching -- Philippines -- Manila -- Aids and devices; Special education -- Philippines -- Manila